Pasak Kayu Kubler Sebagai Alternatif Alat Penyambung pada Konstruksi Kayu di Kalimantan Selatan - Tjitradi, Darmansyah (Department of Civil Engineering, Diponegoro University, 2005)
This paper is as result of the experimental research of a Kübler wood connector on the several types of hard wood in South Kalimantan as the alternative of the connector in the timber structure. This experiment of the Kübler wood connector is done to the three types of the hard wood such as Bangkirai (Shorea Lacvifolia Endert), Simantok (Shorea spec.div) and Merbau (Intsia spec.div), and also the wood that will be connected as the tested supporting specimen is Ulin wood (Eusyderoxylon Zwageri). Every tested specimen is applied the centric compressive axial load in the straight joint, connection with an angle of 120° and connection with an angle of 90° until the connection reaches the failure strength. From the experimental result, it is obtained that on the straight joint, Merbau wood (Class II) having average and characteristic failure strength more than of its Simantok wood (Class II) and Bangkirai wood (Class I). For the angle connection using Simantok wood, the value of its characteristic failure strength is getting higher if the angle of the connection more than 90o, but not for the shifting. Compare with the theoretical value, actually the characteristic failure strength value of Merbau wood is more than the permissible strength, but not for its of Bangkirai and Simantok wood.Keywords: Kübler wood connector, wood connectionPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3894[How to cite: Tjitradi, D., 2005, Pasak Kayu Kubler Sebagai Alternatif Alat Penyambung pada Konstruksi Kayu di Kalimantan Selatan, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 1, pp. 27-38]